Analysis of Aquatic and Land Training on Selected Physical Fitness Variables among Volleyball Players - N. Vijayaragunathan2, R. Kalidasan3, K. Kamalakkannan1* (Recent Research in Science and Technology, 2010)
The purpose of this study was to analyse the aquatic and land training on selected physical fitness variables among Volleyball players. To achieve the purpose 30 physically active and interested undergraduate engineering Volleyball players were selected as subjects and their age ranged between 18 and 20 years. The subjects are categorized into two groups randomly viz.; Aquatic Training group (ATG), land Training group (LTG) and each group had 15 subjects. The experimental group underwent the experimental treatment for 12 weeks, 3 days per week and a session on each day with 90 minutes duration. Speed, endurance and explosive power were taken as variables for this investigation. Fifty meters run, cooper 12 minutes run and standing vertical jump were tests used to collect the relevant data. The data were collected prior and after the experimental treatment. The collected data was analyzed using analysis of covariance (ANCOVA). The result reveals that aquatic training group showed significant improvement in all the selected physical fitness variables.